Answer is: a= -4
STEP
1
:
1
Simplify —————
a + 3
Equation at the end of step
1
:
a 3 1
(————————+—————)-——— = 0
((a2)-9) (a-3) a+3
STEP
2
:
3
Simplify —————
a - 3
Equation at the end of step
2
:
a 3 1
(————————+———)-——— = 0
((a2)-9) a-3 a+3
STEP
3
:
a
Simplify ——————
a2 - 9
Equation at the end of step
3
:
a 3 1
(————————————————— + —————) - ————— = 0
(a + 3) • (a - 3) a - 3 a + 3
Equation at the end of step
4
:
(4a + 9) 1
————————————————— - ————— = 0
(a + 3) • (a - 3) a + 3
Pull out like factors :
3a + 12 = 3 • (a + 4)
Equation at the end of step
6
:
3 • (a + 4)
————————————————— = 0
(a + 3) • (a - 3)
3•(a+4)
——————————— • (a+3)•(a-3) = 0 • (a+3)•(a-3)
(a+3)•(a-3)
a+4 = 0
Subtract 4 from both sides of the equation :
a = -4
Answer:
what is the question asked?
Step-by-step explanation:
3x + (x+3) = 19
4x + 3 = 19
4x = 16
x = 4
y= x+3
y= 4+3
y= 7
Answer:
Step-by-step explanation:
We need to get m on one side all by itself. To achieve this, let's subtract both sides by 1.2 to get .